Advanced Polycrystalline γ′-Strengthened CoNiCr-Based Superalloys - Neumeier, Steffen; Freund, Lisa; Bezold, Andreas; Köbrich, Manuel; Vollhüter, Jan; Hausmann, D.; Solis, C.; Stark, A.; Schell, N.; Pyczak, F.; Felfer, Peter; Gilles, R.; et al. (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2024)
Novel compositionally complex CoNiCr-based superalloys with excellent mechanical properties have been developed, which combine the multiprincipal element nature of high-entropy alloys with the precipitation strengthening in superalloys. A series of advanced polycrystalline γ′-strengthened CoNiCr-based superalloys, called CoWAlloys, with varying contents of Al, W, Ti, Ta, Mo, and Nb are investigated in terms of microstructure, thermophysical properties, yield, and creep strength. The microstructure of all CoWAlloys consists of an fcc solid solution matrix phase (approximate γ composition in at. pct: 50Co–20Ni–20Cr–10X (X = other alloying elements)), which is strengthened by a multicomponent γ′ (Ni,Co)3(Al,Ti,Ta,W,Nb)-based precipitate phase with a very high-volume fraction of around 60 vol pct (approximate γ′ composition in at. pct: 45Ni–30Co–25X). These alloys have high solidus temperatures above 1300 °C and moderate γ′ solvus temperature between 985 °C and 1080 °C leading to a large processing window. The increasing content of γ′-forming elements Ti, Ta, W, and Nb decreases this window, but increases the γ/γ′ lattice misfit and the anti-phase boundary energy, which contribute to a significantly higher yield and creep strength. Their properties are discussed in comparison with conventional polycrystalline Ni-base superalloys and so-called L12-strengthened high-entropy alloys, revealing that the creep strengths of the CoWAlloys are significantly higher. This is due to the reduced strain rate sensitivity of the CoWAlloys due to different underlying deformation mechanisms: By increasing the anti-phase boundary energy, a transition to stacking fault shearing and microtwinning occurs, which leads to the enhanced creep strength. Based on these results, guidelines and strategies for the design of next-generation advanced high-temperature polycrystalline superalloys are proposed. Graphical Abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-03-15

Design and Characterization of a Novel NiAl–(Cr,Mo) Eutectic Alloy - Titz, Katharina; Vollhüter, Jan; Randelzhofer, Peter; Neumeier, Steffen; Göken, Mathias; Wahlmann, Benjamin; Körner, Carolin (Advanced Engineering Materials, 2024)
To enhance the mechanical properties of NiAl–(Cr,Mo) in situ composites for high-temperature structural use, achieving a regular eutectic microstructure is crucial. A novel alloy with a composition of Ni30.6Al36Cr31.4Mo2 is developed that exhibits a significantly reduced solidification interval compared to well-studied alloys such as Ni33Al33Cr28Mo6. This advancement results from using the in-house developed alloy design tool PyMultOpt and Calculation of Phase Diagrams analysis to minimize the solidification interval. The refined alloy demonstrates a theoretical solidification interval of 0 K. These results are verified with differential scanning calorimetry measurements at different heating rates for the new alloy and compared with the established alloy Ni33Al33Cr28Mo6. The small solidification interval leads to a uniform eutectic microstructure consisting of a (Cr,Mo) phase embedded in the NiAl matrix without primary NiAl dendrites present. This indicates that deviating from the stoichiometric NiAl composition results in a significantly lower solidification interval and thus in an actual eutectic composition of the NiAl–(Cr,Mo) system.
CRIS-Team Scopus Importer:2024-04-05
Keywords: alloy development; eutectics; intermetallics; nickel aluminides

Influence of Fe additions on the property profile of high-strength CoNi-based superalloys - Bezold, Alexander; de Jesus Rodrigues, Geovane; Vollhüter, Jan; Nagel, Oliver; Köbrich, Manuel; Stark, A.; Mills, M. J.; Neumeier, Steffen (Journal of Applied Physics, 2025)
CoNi-based superalloys offer excellent high-temperature properties; yet, Co is also a strategic alloying element, and its content should only be as high as necessary. This study investigates Fe as a partial substitute for Co to reduce costs while evaluating its impact on mechanical properties. To evaluate this, we systematically investigate the effect of Fe substitutions on thermophysical properties, microstructure, partitioning behavior, lattice misfit, yield strength, and creep performance of three polycrystalline CoNi-based superalloys derived from CoWAlloy1 (Co-32Ni-12Cr-6Al-3W-2.5Ti-1.5Ta-0.4Si-0.1Hf-0.08B all in at. %). In these alloys, 4, 8, and 12 at. % Co is replaced with Fe. Increasing Fe content results in a gradual reduction in the solvus, solidus, and liquidus temperatures by 3.0, 1.9, and 1.4 °C per at. % Fe, respectively. The γ′ volume fraction and the lattice misfit decrease by about 0.7% and 0.01%, respectively, per at. % Fe substitution for Co. Fe predominantly partitions to the γ matrix, enhancing the partitioning of Co and Ni while reducing that of Al, Cr, and Ta, with no significant effect on Ti and W. Substituting Co with Fe moderately reduces yield and creep strength, primarily due to the decreasing γ′ volume fraction and a transition in the dominant deformation mechanisms from stacking fault shearing and microtwinning to matrix-based deformation as Fe content increases. Beneficial elemental segregation behaviors and localized phase transformations along creep-induced stacking faults remain active in alloys with high Fe content. These findings highlight the potential of Fe alloying to reduce costs while maintaining high-temperature strength in CoNi-based superalloys.
CRIS-Team Scopus Importer:2025-05-30

In situ mechanical testing of hard yet tough high entropy nitride coatings deposited on compliant steel substrates - Kuczyk, Martin; Zawischa, Martin; Krülle, Tim; Vollhüter, Jan; Zeiler, Stefan; Leonhardt, Michael; Kaspar, Jörg; Zimmer, Otmar; Göken, Mathias; Leyens, Christoph; Zimmermann, Martina (Thin Solid Films, 2023)
High entropy nitrides are an interesting material class for wear resistant coatings. Their fracture properties and toughness are of particular interest for future application in tool coatings. Therefore, in situ tensile testing and micro-cantilever experiments were performed on (AlCrTaTiZr)N, (AlCrNbSiTiV)N, (HfNbTaTiVZr)N and (AlTi)N coatings inside a scanning electron microscope. Parallel cracks form during tensile testing from which the fracture toughness was determined via a modified Hsueh and Yanaka model. For this the misfit strain between coating and substrate was treated as an unknown parameter and was fitted to the beginning part of the underlying crack density – applied strain curves. The validity of the model was evaluated by comparing the results with fracture toughness values derived via micro-cantilever bending experiments. A good fit between the data could be observed for three out of four tested coatings. The limitations of the underlying analytical model are presented and discussed. The tested high entropy nitride coatings displayed a promising combination of high hardness and fracture toughness.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Fracture toughness; High entropy nitrides; In situ mechanical testing; Micro-cantilever testing; Tensile testing

Nanostructuring of Nb-Si-Cr Alloys by Electron Beam Melting to Improve the Mechanical Properties and the Oxidation Behavior - Förner, Andreas; Vollhüter, Jan; Hausmann, D.; Arnold, Christopher; Felfer, Peter; Neumeier, Steffen; Göken, Mathias (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2021)
Materials processed by additive manufacturing often exhibit a very fine-scaled microstructures due to high cooling rates in the process. In this study, single-layer surface electron beam melting is used to create very high cooling rates similar to additive manufacturing processes to investigate the resulting microstructure. In the case of Nb-Si-Cr in-situ composites, a nano-scaled eutectic microstructure is beneficial for improving the mechanical and oxidational properties. Fast solidification results in the formation of supersaturated phases of Nbss and Cr2Nb with phase diameters down to 10 nm as well as in the stabilization of the metastable Nb9(Cr,Si)5 phase at room temperature. After processing with different solidification rates, the decomposition of the Nb9(Cr,Si)5 phase has been studied in detail with atom probe microscopy. The stabilization of mixed silicide phases by electron beam melting shows a new pathway for improving hardness and enhancing oxidation resistance of nanostructured eutectic in-situ composites, by which the inherent weaknesses of Nb-Si-Cr can be overcome without further alloying elements. Graphical Abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2021-11-26

Revealing the γ′ and γ″ Phase Fractions of Additively Manufactured and Differently Heat-Treated Nickel-Base Superalloy IN718 by Atom Probe Tomography and Their Impact on Mechanical Properties - Volpato, Guilherme; Vollhüter, Jan; Diepold, Benedikt; Meier, Martin; Pröbstle, Martin; Göken, Mathias; Niendorf, Thomas; Felfer, Peter; Neumeier, Steffen (Advanced Engineering Materials, 2024)
Powder bed fusion using a laser beam (PBF-LB) has great potential for the production of geometrically complex industrial components, allowing for unprecedented geometrical optimization and freedom of design. This potential is particularly relevant in the case of turbine components, whose microstructure and properties are directly affected by the extreme PBF-LB processing conditions. In this context, this study aims to investigate the impact of PBF-LB on the microstructure and mechanical behavior of Inconel alloy 718 (IN718) when heat treated according to different sequences. Atom probe tomography is used to analyze the composition, morphology, configuration, and volume fraction of γ′ and γ″ precipitates as a function of heat treatment conditions. Their impact on the material is evaluated using compression tests under different build orientations. It is shown that when PBF-LB IN718 is subject to solution annealing at 930 °C and subsequently aged, δ needles form in its microstructure at the expense of γ′ and γ″, thus reducing mechanical strength. Such is not the case when the solution annealing step is omitted or when its temperature is increased to 1000 °C, conditions whose superior mechanical behavior have been attributed to a high dislocation density and a large volume fraction of aging phases, respectively.
CRIS-Team Scopus Importer:2025-02-04
Keywords: atom probe tomography; Inconel 718; Ni-base superalloys; precipitation behavior; selective laser melting

Segregation-induced strength anomalies in complex single-crystalline superalloys - Bezold, Andreas; Vollhüter, Jan; Karpstein, Nicolas; Lenz, Malte; Subramanyam, Aparna P.A.; Zenk, Christopher; Hammerschmidt, Thomas; Spiecker, Erdmann; Göken, Mathias; Neumeier, Steffen (Communications Materials, 2024)
Pushing the maximum service temperature of aircraft engines and industrial gas turbines is the major pathway to improve their energy efficiency and reduce CO2 emissions. This maximum is mostly limited by the temperature capability of key-component materials, including superalloys. In this alloy class, segregation of elements facilitates plastic deformation and is generally considered to cause softening during high-temperature deformation. Here, we show that segregation-assisted processes can also lead to strengthening and induce an anomalous increase of the yield strength. Atomic-resolution transmission electron microscopy and density functional theory calculations reveal a segregation-assisted dissociation process of dislocations at precipitate-matrix interfaces in combination with atomic-scale reordering processes. These processes lead to an inhibition of athermal deformation mechanisms and a transition to stacking fault shearing, which causes the strengthening effect. Unraveling these elementary mechanisms might guide a mechanism-based alloy design of future superalloys with enhanced high-temperature capabilities.
CRIS-Team Scopus Importer:2024-02-02

Strain Rate-Dependent Anomalous Work Hardening of a Single-Crystalline CoNi-Base Superalloy - Vollhüter, Jan; Bezold, Andreas; Karpstein, N.; Köbrich, Manuel; Spiecker, Erdmann; Göken, Mathias; Neumeier, Steffen (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2023)
The deformation mechanisms operating in superalloys depend on different parameters such as composition, temperature and deformation rate. So far, the transition from shearing by APB-coupled dislocations to shearing under the formation of stacking faults has been studied exclusively as a function of temperature but not as a function of the strain rate. Therefore, interrupted compression tests with strain rates between 10–3 s−1 and 10–5 s−1 were performed on the single-crystalline CoNi-base superalloy ERBOCo-4 at a temperature of 850 °C. The evolution of the defect structures has been analyzed by conventional transmission electron microscopy. A change of the deformation mechanism from APB-coupled dislocation shearing to stacking fault shearing is found to depend on the strain rate. At lower strain rates, an increased stacking fault density is associated with a higher yield strength and higher work hardening rates at the early stages of plastic deformation due to a very high stacking fault density. After approximately 2.0 pct plastic strain, the stress reaches a plateau and decreases subsequently, which is associated with the formation and thickening of twins as shown by high-resolution scanning transmission electron microscopy. At higher strain rates, the work hardening rate is significantly lower in the early deformation stage. The role of segregation to planar defects and the influence of local phase transformations (LPT) at SESFs is further discussed in reference to the influence of the strain rate. The segregation of W as an η stabilizing element is found to be crucial for the formation of a local phase transformation in ERBOCo-4. At higher strain rates the phase transformation is hindered by insufficient W segregation, resulting in a higher twin density.
CRIS-Team Scopus Importer:2023-02-24

Using Selective Electron Beam Melting to Enhance the High-Temperature Strength and Creep Resistance of NiAl–28Cr–6Mo In Situ Composites - Förner, Andreas; Vollhüter, Jan; Krapf, Anna; Jamjoom, Abdullah Faisal A; Hausmann, Daniel; Wahlmann, Benjamin; Fu, Zongwen; Körner, Carolin; Neumeier, Steffen; Göken, Mathias (Advanced Engineering Materials, 2023)
By increasing the density of interfaces in NiAl–CrMo in situ composites, the mechanical properties can be significantly improved compared to conventionally cast material. The refined microstructure is achieved by manufacturing through electron beam powder bed fusion (PBF-EB). By varying the process parameters, an equiaxed or columnar cell morphology can be obtained, exhibiting a plate-like or an interconnected network of the (Cr,Mo) reinforcement phase which is embedded in a NiAl matrix. The microstructure of the different cell morphologies is investigated in detail using scanning electron microscope, transmission electron microscopy, and atom probe tomography. For both morphologies, the mechanical properties at elevated temperatures are analyzed by compression and creep experiments parallel and perpendicular to the building direction. In comparison to cast NiAl and NiAl–(Cr, Mo), the yield strength of the PBF-EB fabricated specimens is significantly improved at temperatures up to 1,027 °C. While the columnar morphology exhibits the best improved mechanical properties at high temperatures, the equiaxial morphology shows nearly ideal isotropic mechanical behavior, which is a substantial advantage over directionally solidified material.
Created from Fastlane, Scopus look-up
Keywords: additive manufacturing; creep properties; high-temperature strength; in situ composite; intermetallics; NiAl